Adhesion and invasion of Listeria monocytogenes and interaction with Lactobacillus rhamnosus GG after habituation on fresh-cut pear. (July 2017) - Iglesias, M.B.; Viñas, I.; Colás-Medà, P.; Collazo, C.; Serrano, J.C.E.; Abadias, M.
Highlights: L. rham. GG inoculated on pear wedges survived in gastrointestinal tract conditions. L. rham. GG reduced survival of L. monocytogenes in the digestive tract after 7 days of habituation on fresh-cut pear. L. rham. GG modified the virulence of L. monocytogenes. L. rham. GG controlled the growth of L. monocytogenes. Abstract: Several foods are carriers of probiotic bacteria. Most species of the genus Lactobacillus are probiotics and common inhabitants of the human gastrointestinal tract. It is known that they contribute to the health of gastrointestinal tract, but at the same time certain strains can be antagonistic against foodborne pathogens. In this study, we evaluated the effect of Lactobacillus rhamnosus GG on the ability of a strain of Listeria monocytogenes serovar 4b to survive passage through the gastrointestinal tract, and its adhesion and invasion into Caco-2 cells when it was previously habituated on fresh-cut pear stored at 10 °C for 7 days. At the end of the storage, L. rhamnosus GG caused a reduction in the survival of L. monocytogenes in the gastrointestinal tract, and adhesion and invasion into Caco-2 cells. Moreover, it showed an antagonistic activity against L. monocytogenes .